Embedded System Design Student’s Learning Readiness Instruments: Systematic Literature Review - Elfadil, Nazar; Ibrahim, Intisar (Frontiers in Education, 2022)
To evaluate and measure the effects of student’s preparation before studying an embedded system design course, a systematic literature analysis was conducted, spanning publications from 1992 to 2020. Furthermore, evaluating such effects may help to close the gap between academically taught abilities and industry-required skills. The goal of the review was to gather and evaluate all reputable and effective studies that have looked into students’ learning preparation issues and solutions in embedded system design courses. Nonetheless, the purpose of this work was to extract and discuss the key features and methodologies from the selected research publications in order to present researchers and practitioners with a clear set of recommendations and solutions. The findings revealed that no instrument has been developed yet to assess students’ readiness to take up an embedded system design course. Furthermore, the majority of the instruments offered lacked concept clarity.